Manajemen Program Alfamart Class sebagai Strategi Kolaboratif Pengembangan Karier Siswa di SMKN 1 Ponorogo - Adi Pradana; Muhammad Thoyib; M. Syafiq Humaisi (Southeast Asian Journal of Islamic Education Management, 2024)
Vocational high school is a secondary education program that prepares students to work in a particular field. Source Alfaria Triijaya Tbk (Alfamart) with the Alfamart Class program to help students prepare themselves for ready to work. The purpose of this study is to analyze the planning, implementation, and evaluation of the Alfamart Class program in student career development. This study uses a qualitative research type that uses data collection techniques such as interviews, observations, and documentation. At the same time, the data analysis process uses data collection, data condensation, data presentation, and concluding. The results show that the Alfamart Class program is planned before the new school year with involvement from the school community and Alfamart. Program objectives, strategies, and preparation are determined before implementation. The Alfamart Class program was implemented by the East Java Provincial Government, with leaders playing a crucial role in mobilizing members. This program addresses students' career development needs by considering existing supporting and inhibiting factors. Strategies are essensial to achieving goals. The Alfamart Class program at SMKN 1 Ponorogo was evaluated. The evaluation aimed to collect obstacles, identify program obstacles, and carry out follow-up based on the evaluation results. The evaluation showed an increase in students' knowledge and skills. 85% of the students continue their careers at Alfamart.